Do mites evolving in alternating host plants adapt to host switch?. (21st July 2014) - Magalhães, S.; Cailleau, A.; Blanchet, E.; Olivieri, I.
Abstract A fluctuating environment may be perceived as a composition of different environments, or as an environment per se, in which it is the fluctuation itself that poses a selection pressure. If so, then organisms may adapt to this alternation. We tested this using experimental populations of spider mites that have been evolving for 45 generations in a homogeneous environment (pepper or tomato plants), or in a heterogeneous environment composed of an alternation of these two plants approximately at each generation. The performance (daily oviposition rate and juvenile survival) of individuals from these populations was tested in each of the homogeneous environments, and in two alternating environments, one every 3 days and the other between generations. To discriminate between potential genetic interactions between alleles conferring adaptation to each host plant and environmental effects of evolving in a fluctuating environment, we compared the performance of all lines with that of a cross between tomato and pepper lines. As a control, two lines within each selection regime were also crossed. We found that crosses between alternating lines and between pepper and tomato lines performed worse than crosses between lines evolving in homogeneous environments when tested in that environment. In contrast, alternating lines performed either better or similarly to lines evolving in homogeneous environments when tested in a fluctuating environment. Our results suggest that fluctuating environments are more than the juxtaposition of two environments. Hence, tests for adaptation of organisms evolving in such environments should be carried out in fluctuating conditions.